Determinan Kemiskinan Wilayah Kepulauan DI Indonesia - intan biduri; Joan Marta (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This research aims to examine the influence of human capital, financial capital, economic structure, and regional dummy variables on the poverty level of island regions in Indonesia. The analysis method used in this research is multiple linear regression analysis. The results of this study indicate that all independent variables collectively have a significant impact on the poverty level as the dependent variable. Partially, human capital has a negative and significant impact on the reduction of poverty levels, financial capital has a negative and significant impact on the reduction of poverty levels, while the economic structure has a positive but not significant impact on the reduction of poverty levels. Human capital interacted with the area dummy has a negative and significant effect at the 10% level on the reduction of poverty levels, financial capital interacted with the area dummy has a negative but not significant impact on the reduction of poverty levels, the economic structure interacted with the area dummy has a negative but not significant impact on the reduction of poverty levels, and the area dummy has a positive and significant impact at the 10% level indicating a difference between island regions and non-island regions.